Control of active suspension system considering nonlinear actuator dynamics. Issue 2 (January 2018) - Kilicaslan, Sinan
Abstract Application of the state-dependent Riccati equation and approximating sequence of Riccati equation techniques for the control of active suspension system considering nonlinear actuator dynamics will be investigated. First, equation of motion of the vehicle model is written in terms of the nonlinear state equations. Then, a performance index is formed for the minimization of the acceleration of the sprung mass, suspension deflection, velocity of the sprung mass, tire deflection, velocity of the unsprung mass, pressure decrease through the piston, and rate of pressure decrease through the piston. A sinusoidal bump and road roughness are considered as the road disturbances. After that, control input is expressed in terms of the Riccati differential equation variables and the state variables. Finally, quarter vehicle suspension system model of a Ford Fiesta Mk2 is taken into consideration in numerical simulations to test the performances of the both techniques. The results are compared to those of equivalent passive suspension system.